(untitled) (CIPEEX, 2025)
The principle of the primacy of the decision on the merits, introduced by Ronald Dworkin, is based on the idea that judicial decisions should prioritize the full resolution of the issues debated, for the sake of the coherence and integrity of the legal system. This principle is supported by Article 4 of the new Code of Civil Procedure (CPC), which establishes the right of the parties to obtain a full resolution of the merits within a reasonable time. In this context, the question arises as to the applicability of this principle to extraordinary instances. Given the importance of the principle of the primacy of decisions on the merits in guaranteeing the effectiveness of the legal system, the following problem arises: Can the principle of the primacy of decisions on the merits be applied to extraordinary instances? The general objective of this project is to analyze whether the principle of the primacy of decisions on the merits can be applied to extraordinary instances of the judicial system. The following specific objectives were formulated: i) to discuss the doctrinal concept and the legal provision of the principle of primacy of the decision on the merits; ii) to address the application of the principle of primacy of the decision in the ordinary instances of the judicial system; iii) to analyze the possibility of applying the principle of primacy of decisions on the merits in extraordinary instances, considering their characteristics and peculiarities. The methodology of this study will include a bibliographical review to discuss the doctrinal concept and the legal provision of the principle of primacy of the decision on the merits. Legal works, academic articles and relevant legislation will be consulted to support the theoretical analysis of the subject. In addition, jurisprudential research will be carried out to identify relevant cases that address the application of this principle in extraordinary instances. This project is justified by the importance of discussing the application of the principle of the primacy of the decision on the merits in all instances of the judicial system. Considering the importance of this principle for the effectiveness of the legal system, it is essential to investigate whether it should also be observed in extraordinary instances, guaranteeing the full resolution of issues debated at all levels of jurisdiction. It is hoped that this study will provide support for understanding the applicability of the principle of the primacy of the decision on the merits in the extraordinary instances of the judicial system. In addition, it is hoped that this project will contribute to the development of proposals and strategies to improve the effectiveness of the judicial system, guaranteeing the full resolution of issues debated at all levels of jurisdiction.